Offshore outsourcing of professional services: A transaction cost economics perspective - Ellram, Lisa M.; Tate, Wendy L.; Billington, Corey (Journal of Operations Management, 2008)
AbstractThis research utilizes the framework of transaction cost economics (TCE) to develop an understanding of how firms manage the costs and risks of offshore outsourcing of professional services. This research examines the perspectives of eight organizations through interviews with 10 high‐ranking supply management executives. The paper first explores the rationale for offshore outsourcing among the organizations studied. Using the tenants of TCE, this paper postulates that fixed costs of establishing the relationship dominate the variable costs of day‐to‐day transactions, and that organizations will not offshore outsource areas where there is high perceived degree of unmanageable risk. The paper expands on themes provided by TCE and offers some lessons learned, and guidelines for managing and controlling offshore outsourced services relationships.